(untitled) (Bulletin of Innovative Research, 2026)
This article is devoted to an in-depth and comprehensive analysis of scientifically grounded agro-technical measures for cultivating saffron (Crocus sativus), a plant of high medicinal value. In particular, it examines key technological factors such as planting rate, planting time, fertilization system, and irrigation regime. Based on the biological, physiological, and morphological characteristics of saffron, a system of agro-technical parameters ensuring its optimal development has been developed. The study also reviews the interrelationships among major ecological, agrochemical, and hydrotechnical factors affecting crop productivity.